A 3D model for chimney formation in sedimentary basins. (April 2020) - Wangen, Magnus
Abstract: This paper introduces a 3D model for chimney formations in tight rocks in sedimentary basins. This is an adaption of a model for hydraulic fracturing in an anisotropic stress field by fluid injection (fracking). The model assumes that a chimney formation is triggered and sourced by overpressure build-up in permeable units, such as reservoirs or aquifers. Cells in the numerical models fracture when the fluid pressure exceeds the least compressive stress and a random rock strength. Chimney growth is represented by chains of cells (branches) that emanate from the base of the cap rock. The branches have an enhanced permeability during ascension, because the fluid pressure in the fracture network is greater than the least compressive stress. When the branches reach the hydrostatic surface, the fluid pressure drops below the fracture pressure and the fracture network closes. The reservoir is drained by the branches in the closed fracture network that reaches the seafloor. The model produces pipe-like structures and chimneys as accumulations of branches that reach the surface. The degree of random rock strength controls how pipe-like the chimneys become. Chimney formation stops when the rate of fluid leakage through the chimneys surpasses the production of excess fluid by the overpressure-building process. A "low" permeability of the chimney branches produces wide chimneys with many branches, and a "high" permeability gives narrow chimneys made of just a few branches. The model is demonstrated in a setup that could be relevant for the chimneys observed in the cap rock over the Utsira aquifer in the North Sea. By using the proposed model, the permeability of such chimneys is estimated to be of the order of 10 μ D. Highlights: A algorithmic approach is proposed for the modelling of chimney and pipe formation in 3D. The approach is demonstrated on data similar to observations from the North Sea. It is shown how chimney growth and final chimney shape depends on the chimney permeability. The final chimney permeability is estimated.